2007
DOI: 10.1002/pssc.200674814
|View full text |Cite
|
Sign up to set email alerts
|

High temperature growth of AlN film by LP‐HVPE

Abstract: AlN films were grown on AlN/sapphire templates at 1400–1500 °C using low‐pressure hydride vapor phase epitaxy (LP‐HVPE). Compared to the step‐flow growth of AlN film at 1200 °C with growth rate of 2.1 μm/h, AlN films with atomic steps were obtained at 1400–1500 °C even with high growth rate. For the AlN film grown at 1450 °C with growth rate of 14.3 μm/h, the RMS value is 0.75 nm and the FWHM values of (0002) and (10‐12) X‐ray rocking curve (XRC) are 351 and 781 arcsec, respectively. Since the FWHM value of (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In recent years, our group has succeeded in growing thick AlN layers by HVPE using the aluminum trichloride (AlCl 3 ) and NH 3 as an Al and N precursors, respectively [8][9][10]. Also, several groups tried to grow AlN layers by same methods [11]. However, the growth temperature for AlN by HVPE was restricted by the softening point of quartz reactor at around 1200 1C.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, our group has succeeded in growing thick AlN layers by HVPE using the aluminum trichloride (AlCl 3 ) and NH 3 as an Al and N precursors, respectively [8][9][10]. Also, several groups tried to grow AlN layers by same methods [11]. However, the growth temperature for AlN by HVPE was restricted by the softening point of quartz reactor at around 1200 1C.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, several research groups have reported the growth of AlN layer on a sapphire or SiC substrate by HVPE [3][4][5][6][7]. We have recently demonstrated the fabrication of a thick AlN layer by lowpressure HVPE (LP-HVPE) on an AlN/sapphire template [8] and have also improved the crystal quality and surface morphology by high-temperature (41300 1C) growth [9]. However, the formation of cracks due to the large difference in thermal expansion coefficient between AlN and sapphire is considered a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…By ω-scan X-ray rocking curve (XRC) measurements, full-width at half-maximum (FWHM) values for (0002) and (10-10) diffractions of the 5μm groove-width were 223 and 630 arcsec, and the 15μm groove-width were 220 and 525 arcsec, respectively. The estimated screw and edge dislocation densities of the 5μm groove-width were 5.2x10 7 cm -2 and 1.1x10 9 cm -2 , and the 15μm groove-width were 4.6x10 7 cm -2 and 7.4x10 8 cm -2 , respectively [3]. In order to control the height of void -bottoms (h b ), we fabricated AlN templates with various stripe pattern and thick AlN layer were grown by HVPE.…”
Section: Contributed Articlementioning
confidence: 99%
“…In order to achieve high efficiency AlGaN-based DUV-LEDs, the development of a low threading dislocation density (TDD) AlN template is quite important. Hydride vapor phase epitaxy (HVPE) is expected for fabricating thick AlN film for the substrate [3], but it is still difficult for growth of the high-quality and crack-free thick AlN due to large difference thermal expansion coefficients and lattice constants between AlN and sapphire substrate.…”
mentioning
confidence: 99%